ANALYSIS OF THE RELATIONSHIP BETWEEN EFFECTIVE COMMUNICATION WITH STUDENTS LEARNING OUTCOMES IN PHYSICS LESSON CLASS XI MIA SMA AL FITYAN MEDAN TA 2020/2021 - Rahman, Muhammad; Sani, Ridwan Abdullah ((IPER) Indonesian Physics Education Research, 2021)
This study aims to determine the relationship between effective communication and student learning outcomes in Physics class XI MIA SMA Al Fityan Medan T.A 2020/2021. The research method used is descriptive quantitative with the type of research used is correlational research. To obtain the necessary data, in this study the researchers used a data collection tool in the form of a questionnaire. For effective communication variables, an average score of 74 is in the medium category, while student learning outcomes in Physics class XI MIA SMA Al Fityan Medan get an average score of 87 and are in the medium category. In this study, the correlation coefficient between effective communication and student learning outcomes in Physics class XI MIA SMA Al Fityan Medan was obtained rcount = 0.515 with rtable = 0.162 at the significance level = 0.05, thus rcount > rtable or rcount value is more greater than rtable, then effective communication has a positive relationship with student learning outcomes in Physics subjects. The coefficient of determination (KD) of effective communication is 26.6%. Based on the data analysis and discussion conducted, it can be concluded that the hypothesis which states "there is a positive and significant relationship between effective communication and student learning outcomes in Physics class XI MIA SMA Al Fityan Medan T.A 2020/2021" can be accepted.Keywords: Effective Communication, Student Learning Outcomes, SMA Al Fityan Medan